SIMULATION MODELING IN MODERN RESEARCH - Mykhaylyuta, Sergiy (Sworld-Us Conference proceedings, 2023)
The paper solves the problem of choosing hardware and software tools for the effective solution of scientific research and engineering problems, in connection with which a brief review of hardware and software tools used to build systems of simulation ful